Effect of Milling Time and Multi-walled Carbon Nanotube Content on Structure and Properties of an Al-Cu-Mg/MWCNT Composite Produced by Different Dispersion Methods and Powder Metallurgy - Ozer, Hayrunnisa; Varol, Temel; Canpolat, Ozlem (Springer, 2025)
The effectiveness of multi-walled carbon nanotubes (MWCNTs) dispersion in Al-Cu-Mg alloy matrix composites reinforced with carbon nanotubes is one of the most important factors influencing the homogeneity and the mechanical and physical properties of the composite. This study applied conventional, magnetic, ball milling and ultrasonic dispersion techniques to uniformly distribute MWCNTs. Most effective dispersion occurred after 45 min in ultrasonic stirring. Al-Cu-Mg alloy powder was reinforced with MWCNTs at four rates (0.125, 0.25, 0.5 and 1 wt.%) and three ball milling times (0.5 h, 1.5 h and 3 h) to make Al-Cu-Mg/MWCNT composites. After 3 h of milling, the composite powders had an average particle size of 10-58 mu m. The maximum density value of 0.125 wt.% MWCNTs reinforced composites milled for 3 h is 2.733 g/cm(3), while the minimum density 1 wt.% MWCNTs reinforced composites milled for 0.5 h is 2.609 g/cm(3). The tensile strength increased gradually as the amount of MWCNTs increased, and it reached a maximum value of 202 MPa for 0.5 wt.% MWCNTs reinforced Al-Cu-Mg alloy matrix composites. This is an increase of 61% in comparison with the tensile strength of the Al-Cu-Mg alloy produced under the same conditions (125.6 MPa).
Keywords: Al-Cu-Mg alloy; ball milling; multi-walled carbon nanotubes; metal matrix composites; ultrasonic dispersion